Silence as Resistance: A Critical Discourse Analysis of Benjamin Netanyahu’s United Nations General Assembly 2025 Speech and the Audience Walkout - Fantasiya Nurul Huda (Lexicon, 2026)
This study analyzes a qualitative Critical Discourse Analysis (CDA) to examine Benjamin Netanyahu’s 2025 UN General Assembly speech and the audience’s performative response. Using Fairclough’s three-dimensional framework, the analysis is conducted at the levels of textual features, discursive practice, and social practice. The data consist of selected excerpts from the official speech transcript and documented instances of the coordinated walkout by Arab and pro-Palestinian delegations. Textual analysis focuses on evaluative lexical choices such as “finish the job,” “defend ourselves,” and “civilized world,” which function to legitimize Israel’s actions and construct moral justification. The walkout is analyzed as a counter-discursive practice that disrupts this framing and challenges assumed international consensus. The study demonstrates how political rhetoric and non-verbal dissent interact to negotiate power and legitimacy in global diplomatic contexts.